STUDY OF CONSUMER ACCEPTANCE OF INSTANT REBON Shrimp Shrimp (Acetes sp.) SHIPPING WITH DIFFERENT TYPES OF CHILLIES - Abdurrahman Afifi; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstrakThe purpose of this study was to determine the proximate difference of instant shrimp paste shrimp paste (Acetes sp.) with the addition of different types of chili and to determine the level of consumer acceptance of making instant chili paste with different types of chili treatment. The method used is an experimental method by conducting experiments on consumer acceptance of the instant rebon shrimp paste chili with red and green chili types with a weight of 84,6,6g or 47% of the weight of the shrimp paste that you want to make. Parameters assessed by proximate and organoleptic analysis were appearance, aroma, taste and texture performed by 80 untrained people, moisture content, ash content, fat content, protein content and carbohydrate content. The results showed that making chili paste using red chili was more preferred by consumers than green chili chili paste. The formulation for making red chili paste with 33% water content, 77% ash content, 83.49% fat content, 46.18% protein content and 52.33% carbohydrate content.Keywords: Acetes sp, red chili, green chili, instant, shrimp paste.